Михаил Булгаков в Художественном театре - Смелянский Анатолий Миронович (Искусство, 1989)
Экземпляры: ФИЛ (20110816) / Инвентарный номер: 952273 / Цена: 3.40 / Сис.шифр: 83.3(2=Рус)7-8 / Авт.знак: С 50 / ГРНТИ: 17 / ББК: 83.3(2=Рус)6-8